De-novo assembly of mango fruit peel transcriptome reveals mechanisms of mango response to hot water treatment - Luria, Neta (BMC Genomics, 2014)
BACKGROUND: The mango belongs to the genus Mangifera, consisting of numerous tropical fruiting trees in the flowering plant family, Anacardiaceae. Postharvest treatment by hot water brushing (HWB) for 15–20 s was introduced commercially to improve fruit quality and reduce postharvest disease. This treatment enabled successful storage for 3–4 weeks at 12°C, with improved color and reduced disease development, but it enhanced lenticel discoloration on the fruit peel. We investigated global gene expression induced in fruit peel by HWB treatment, and identified key genes involved in mechanisms potentially associated with fruit resistance to pathogens, peel color improvement, and development of lenticel discoloration; this might explain the fruit’s phenotypic responses. RESULTS: The mango transcriptome assembly was created and characterized by application of RNA-seq to fruit-peel samples. RNA-seq-based gene-expression profiling identified three main groups of genes associated with HWB treatment: 1) genes involved with biotic and abiotic stress responses and pathogen-defense mechanisms, which were highly expressed; 2) genes associated with chlorophyll degradation and photosynthesis, which showed transient and low expression; and 3) genes involved with sugar and flavonoid metabolism, which were highly expressed. CONCLUSIONS: We describe a new transcriptome of mango fruit peel of cultivar Shelly. The existence of three main groups of genes that were differentially expressed following HWB treatment suggests a molecular basis for the biochemical and physiological consequences of the postharvest HWB treatment, including resistance to pathogens, improved color development, and occurrence of lenticel discoloration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-15-957) contains supplementary material, which is available to authorized users.